TRANSFORMASI PEMBELAJARAN AKTIF MELALUI DISCOVERY LEARNING BERBANTUAN MEDIA FLIP-BOOK TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK - Wawan Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low problem-solving abilities of Indonesian students as reflected in the results of the Programme for International Student Assessment (PISA) 2022 and the continued dominance of conventional learning that causes students to be passive and dependent on educators. This study aims to analyze the effectiveness of the Discovery Learning model assisted by Flipbook media and learning motivation on students' problem-solving abilities. The study used a quantitative approach with a quasi-experimental design through a Nonequivalent Control Group Design and a 2x2 factorial design. The research sample consisted of 120 students selected using random sampling. Data collection was carried out through problem-solving ability tests, learning motivation questionnaires, and documentation, then analyzed using normality tests, homogeneity tests, independent sample t-tests, and Two-Way ANOVA assisted by SPSS 27.0. The results showed that the Discovery Learning model assisted by Flipbook media had a significant effect on students' problem-solving abilities with a value of F = 132.505 and p = 0.000. Learning motivation also had a significant effect with an F value of 9.875 and p = 0.002. There was also a significant interaction between the learning model and learning motivation with an F value of 10.157 and p = 0.002. The experimental group achieved a higher average problem-solving ability than the control group. The R Squared value of 0.596 indicates that the learning model and learning motivation were able to explain 59.6% of the variation in students' problem-solving abilities. This study confirms that the integration of innovative learning models based on digital technology can improve critical thinking and problem-solving skills in 21st-century students. Further research is recommended to develop the use of Flipbook media in different materials and educational levels by involving additional variables such as creativity and digital literacy.